Origenes rediuiuus : la découverte des Homélies sur les Psaumes dans le Cod. Gr. 314 de Munich - Perrone, Lorenzo (Revue d'études augustiniennes et patristiques, 2013)
After a short presentation of the circumstances of the discovery in April 2012 of Codex Monacensis Graecus 314 (Bayerische Staatsbibliothek, Munich) by Marina Molin Pradel, this article examines the external and internal criteria supporting the attribution to Origen of the 29 anonymous homilies on the Psalms. External evidence is provided first of all by Jerome’s Letter 33, whose list largely corresponds to Cod. Gr. 314 (especially with regard to the long series of nine sermons on Psalm 77). Then we have the first four Latin homilies on Psalm 36 translated by Rufinus and also an important fragment taken from the second homily on Psalm 15 and preserved in his translation of the Apology of Origen by Pamphilus and Eusebius of Caesarea. Moreover we dispose of several excerpts in the catenae on the Psalms. Also inner criteria come to support the attribution to Origen: 1) the stylistic and literary aspects; 2) the historical and doctrinal background; 3) the personality of the preacher. These homilies offer precious light not only for the study of Origen’s preaching activity, but also for a better analysis of his important interpretation of the Psalms and the evolution of his thought.